Social media use for work during non-work hours and turnover intention: the mediating role of burnout and the moderating role of resilience - Fang, Zhenbang; Bao, Yuanjie; Hua, Min (Frontiers in Psychology, 2024)
This study uses survey data from 504 Chinese teachers to investigate the relationship between social media use for work during non-work hours (SMUNW) and turnover intention, focusing on the mediating role of burnout and the moderating role of resilience in this relationship.In November of 2023, online survey links were sent to 529 teachers from Shandong Province, China, asking them to report their perceptions of SMUNW, burnout, resilience and turnover intention. A sample of 504 valid responses was obtained. SPSS 26.0 and Hayes' PROCESS MACRO for SPSS were used to conduct analysis for hypotheses testing.The results revealed that burnout acts as a mediator in the relationship between SMUNW and turnover intention. In addition, resilience moderated the relationship between SMUNW and burnout such that when resilience was higher, the relationship between was alleviated. Moreover, resilience moderated the indirect relationship between SMUNW and turnover intention through burnout such that when resilience was higher, the indirect relationship was alleviated.